2011
DOI: 10.1891/0889-8391.25.4.235
|View full text |Cite
|
Sign up to set email alerts
|

How Should Mental Health Professionals Respond to Outbreaks of Mass Psychogenic Illness?

Abstract: The management of episodes of mass psychogenic illness poses a challenge for mental health professionals who have a history of inadvertently exacerbating episodes. This article identifies the two major presentation types (anxiety vs. motor), discusses their significance as a public health issue, and offers guidelines for responding to outbreaks and addressing the media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, there are some strategies that can be employed to help limit the spread of anxiety and symptoms. Bartholomew and Muniratnam89 highlight the importance of staying calm and offering reassurance to those affected, separating those with symptoms from others, if possible, to prevent line-of-sight and sound transmission, and avoiding asking leading questions about specific symptoms. In addition, it is suggested that if possible the source of anxiety should be dealt with, and the reality of patients’ symptoms should be acknowledged.…”
Section: Health Scaresmentioning
confidence: 99%
“…However, there are some strategies that can be employed to help limit the spread of anxiety and symptoms. Bartholomew and Muniratnam89 highlight the importance of staying calm and offering reassurance to those affected, separating those with symptoms from others, if possible, to prevent line-of-sight and sound transmission, and avoiding asking leading questions about specific symptoms. In addition, it is suggested that if possible the source of anxiety should be dealt with, and the reality of patients’ symptoms should be acknowledged.…”
Section: Health Scaresmentioning
confidence: 99%
“…In these types of cases, groups of people develop a constellation of symptoms that are suggestive of an organic illness but without a clearly identified etiology (Jones et al, 2000). A predominant feature in mass psychogenic illness is the rapid emergence of symptoms often of members within a cohesive social unit (Bartholomew & Muniratnam, 2011) who are typically under physical or psychological stress who suddenly believe that they have been made ill by some external/environmental cause. Examples include the medical consequences of a water pollution accident in Camelford, England (David & Wessely, 1995), in the absence of objective evidence that the pollution could create such physical symptoms, and a purported case of a constellation of subjective physical symptoms that were attributed to toxic exposure at a high school in Tennessee (Jones et al, 2000).…”
Section: Relevant Psychological Theory and Principlesmentioning
confidence: 99%